Takhrij and Syarah Hadith of Chemistry: The Prohibition of gold rings for men - Tanti Nurani; Hofifah Astuti; Naan Naan; Ilim Abdul Halim; Adi Mulyana Supriatna (UIN Sunan Gunung Djati Bandung, 2021)
This purpose of this research is to discuss the hadith of the Prophet Saw. about the prohibition of gold rings for men. This research method is a qualitative type through the approach of takhrij and syarah hadith with chemical analysis. The results and discussion of this research were the dangers of overuse of gold rings for men in terms of health. The conclusion of this research is takhrij and syarah hadith of the Prophet Saw. about prohibition of gold rings for men because it has a harmful effect on health.